Kajian Teologi Praktis Persepuluhan dan Kesadaran Memberi Persembahan di Jemaat GMIM Imanuel Toraget Wilayah Langowan Dua - Supit, Elma; Sendow, Mieke Nova; Tamaweol, Roy Dekky (LIMMUD: Jurnal Ilmu Keagamaan dan Sosial Humaniora, 2025)
This study examines the practice of tithing in GMIM Imanuel Toraget Congregation, Langowan Dua District, from a practical theology perspective and the factors influencing congregational awareness in giving offerings. The main issue identified is the low level of understanding among church members regarding tithing, influenced by limited church teachings, the perception of tithing as a financial burden, and economic factors. This research employs a qualitative method with a descriptive approach, collecting data through observation, interviews, and documentation. The findings indicate that the congregation’s limited theological understanding and lack of church education contribute to the low practice of tithing. To enhance awareness, the church needs to strengthen practical theological education, develop a more systematic church policy, and provide economic support that enables members to give joyfully